MACROZOOBENTHIC COMMUNITIES IN THE EASTERN PART OF THE EASTERN BOSPHORUS STRAIT (PETER THE GREAT BAY, JAPAN SEA) - A. V. Moshchenko; T. A. Belan; V. V. Ivin (Известия ТИНРО, 2018)
In total, 146 species of macrozoobenthos belonged to 11 taxonomic groups are found in the surveyed area in the eastern part of the Eastern Bosphorus Strait. Polychaetes have the highest species number, followed by bivalves and amphipods with five times less number of species. Polychaetes and bivalves have the highest occurrence, too, gastropods and amphipods occur frequently, as well. Bivalves dominate by biomass, but polychaetes — by their abundance. Benthos of the Patrokl Bight at the northern coast is poor relatively to the southern part of the strait at Russky Island because of low species diversity of amphipods, gastropods and decapods. Four macrozoobenthic communities are defined with the following titular species: Acila insignis + Scalibregma inflatum, Ophiura sarsi + Scoloplos armiger, Ennucula tenuis + Nicolea sp., and Dipolydora cardalia + (Melinna elisabethae or Maldane sarsi). Besides, Echinocardium cordatum dominates at the single station in the internal Patrokl Bight and Protocallithaca adamsi dominates at the single station in the Zhitkov Inlet. Majority of these communities are quite diverse and abundant. All of them, except the last case, are undisturbed or slightly disturbed and possess in good or moderate ecological state. In the case of the Zhitkov Inlet, the impoverished community of P. adamsi is considerably disturbed due to anthropogenic impact. Differentiation between the majority of communities is noted along gradients of natural environmental factors, as depth and fractional composition of bottom sediments. All conclusions are statistically significant and based on the results of consequential use of the factor and cluster analysis, non-metric multidimensional scaling and constrained correspondence analysis with bootstrap and randomization procedures. There is noted that the bottom communities in this area are subjected to rather significant contamination that supposedly causes decreasing of their stability and they may change their species composition and abundance under additional negative impact.